Knowledge and attitude of Iraqi pharmacists in Baghdad community toward ‎adverse drug reactions monitoring - Mohammed, Samer Imad; Abdul Al-razaq, Amna Fouad (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives:Adverse drug reactions (ADR‎s) can lead to many complications associated with the use of medications .In Iraq where a wide range of medications misused widely due to different reasons, the Iraqi pharmacovigilance program started out few years ago to collect information about adverse drugs reactions and since the success of this program depends on the effective participation of all medical staffs including pharmacists in this program. This study aimed to assess the knowledge, attitude, and degree of awareness of Iraqi pharmacists in Baghdad community toward adverse drugs reactions monitoring and pharmacovigilance program. Methods: This study was a cross-sectional descriptive survey based on individual questionnairethat administered in the English language to a convenience sample of 150 pharmacists working in 3 colleges of pharmacy, 20 community pharmacies and 3 hospitals situated in different areas of Baghdad which are the capital of Iraq. The questionnaire consists of three parts that collect demographic data on the ‎participants and their knowledge, attitudes toward Pharmacovigilance‎. Results: Although about (62%) of pharmacists have observed ADRs in their practice‎ only half of the respondents have heard about the term pharmacovigilance, 48% were aware of the national PV program ‎‎.Moreover , (‎47.33%‎) of the respondents mentioned that ADRs associated with herbal ‎products should not be reported. Although ‎79% of the respondents thought that reporting ADRs is a pharmacist's duty nevertheless 82% of them ‎thought that ADRs reporting in Iraq is not widely promoted by the relevant authority .The study showed a high tendency for participation in an adverse drug reaction monitoring program. Interestingly,‎ 60% of respondents report that their workplace ‎doesn't encourage them for reporting ADRs, while 48% of respondents indicated that they don't ‎have enough time for reporting ADRs and 38% of them declared their fearing of facing ‎legal problem from that . ‎ Conclusion: Iraqi pharmacists although have a high tendency in participation in ADR monitoring program but have a poor knowledge about pharmacovigilance practices; they lack ‎understanding of the details about the national PV system and ADRs ‎reporting process and may need more information on how ADRs ‎reporting are performed. Keywords: Knowledge, Attitudes, Adverse drug reactions, Pharmacovigilance.